Hubungan Pengetahuan Ibu Balita Usia 7-36 Bulan Tentang Asi Eksklusif Dengan Kegagalan Ibu Dalam Memberikan Asi Eksklusif - Muniati murniati; Yuliana Puspita Dewi (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2017)
Knowledge of Exclusive Breast Milk affects the mother's mindset in givingExclusive Breastmilk to her baby. According to data from posyandu of Jalen Village,Balong District, Ponorogo District, 2016 until October for Exclusive Breastfeedingachievement of 8% from target 60%. Based on preliminary study results from 10respondents found 3 mothers understand about Exclusive breastfeeding and exclusivebreastfeeding because breast milk is very beneficial for the baby, while 7 mothers do notunderstand about exclusive breastfeeding and not give exclusive breastfeeding forvarious reasons. To know the relationship of knowledge of mother toddlers aged 7-36months about Exclusive breastfeeding with mother failure in giving exclusivebreastfeeding. The type of this research is analytic with cross sectional approach byusing acidental sampling technique. Population in this research is all mother of childrenaged 7-36 months in Posyandu Jalen Village a number of 40 respondents with thenumber of samples 31 respondents in January 2017. Independent variables are maternalknowledge and dependent variable is a failure Mother of toddlers. His instruments usedquestionnaires and interviews. Data analysis using chi square significant is determinedwith value ˂0,05. From the results of the study, less knowledge about Exclusive BreastMilk most of the 16 respondents (51.6%) had and to provide Exclusive Breast Milk mostof the respondents (67.7%) failed. there is correlation of knowledge of mother of toddlerage 7-36 month tengtang exclusive breastfeeding with mother failure in giving exclusivebreast feeding ρ = 0,024 with significance level ρ˂0,05 ho is rejected which means andlevel of relationship of moderate Ie 0.441 (0.400-0.599).Judging from the results of theabove research is expected to have good knowledge of mothers, that is made thecounseling-extension and seek information from various sources so that the mother'sfailure to provide an exclusive ation to her baby to be low.